2004
DOI: 10.2166/wh.2004.0002
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the survival of F+RNA and F+DNA coliphages in lake water microcosms

Abstract: The survival of seven F+RNA phages (MS2 Group I ATCC type strain, two Group I environmental isolates, a Group II environmental isolate, a Group III environmental isolate, and two Group IV environmental isolates) and six F+DNA phages (M13, fd, f1, and ZJ/2 ATCC type strains, and two environmental isolates) were examined in microcosms using a surface drinking water source. Phages were spiked into replicate aliquots of a source water at about 20,000 pfu/ml. Replicate spikes were incubated at 4 and 20 degrees C an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
48
2
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 14 publications
6
48
2
1
Order By: Relevance
“…The F-specific RNA belonged to genogroups (genotypes) I and II, whereas genogroups II and III are the most abundant genogroups in the raw sewage of the area (45). These results seem to confirm the results of previous reports indicating a higher persistence of genogroups (genotypes) I and II in river (43) and lake (24) water. In addition, these data plus the changes in the relative proportion between indicators point out that, as well as dilution, differential inactivation played an important role in the final conformation of the microbial populations in the area studied.…”
Section: Discussionsupporting
confidence: 88%
“…The F-specific RNA belonged to genogroups (genotypes) I and II, whereas genogroups II and III are the most abundant genogroups in the raw sewage of the area (45). These results seem to confirm the results of previous reports indicating a higher persistence of genogroups (genotypes) I and II in river (43) and lake (24) water. In addition, these data plus the changes in the relative proportion between indicators point out that, as well as dilution, differential inactivation played an important role in the final conformation of the microbial populations in the area studied.…”
Section: Discussionsupporting
confidence: 88%
“…F ϩ DNA coliphages were slightly more abundant than F ϩ RNA coliphages in untreated sludge, and the thermal inactivation experiments indicated that they are as heat resistant as the group I F ϩ RNA phages. F ϩ DNA coliphages have been found in the environment in summer months and are more stable than F ϩ RNA coliphages over different seasonal temperatures, suggesting that they may have some resistance to heat (21). It is possible that F ϩ DNA coliphages are more susceptible to matrix effects in biosolids, which would not have been manifested in the thermal inactivation experiments using laboratory medium.…”
Section: Discussionmentioning
confidence: 99%
“…Reportedly, FDNA phages are more resistant than FRNA phages to sunlight exposure (37), and in some studies they have been detected at higher concentrations than the FRNA phages, especially during the summer and fall (9). These observations suggest that FDNA phages could be potentially useful for year-round source tracking studies (9,25,26). In contrast to FRNA phages, however, FDNA coliphages are a genetically homogeneous group of viruses and very little is known about their ecology.…”
mentioning
confidence: 99%